INCREASING THE EFFICIENCY OF TREATMENT OF INFLAMMATORY PERIODONTAL DISEASES IN PATIENTS WITH THYROID DISEASES - Yusubova, Sh.R.; Mamedov, F.Y. (World of Medicine and Biology, 2021)
A comprehensive periodontal examination and questionnaire survey of 150 people suffering from thyroid dysfunction and chronic generalized periodontitis (the average age of patients was 31.6±0.46 years) and 150 practically healthy persons of the same age and sex were carried out. The level of MDA concentration after completion of the course of basic therapy in all groups was 0.71±0.03 nmol/ml, 1.30±0.03 nmol/ml, and 2.89±0.15 nmol/ml, respectively, in the main group. the control group and the comparison group. The results of biochemical studies showed a less pronounced trend in comparison with the main group of patients in the normalization of the content of S-IgA immunoglobulins – 0.46±0.023 mg/l. The fact of a more pronounced increase in the amount of sIgA in saliva after the use of hyaluronic acid is associated with a significant activation of immunological processes in the oral cavity.
Keywords: periodontal disease; hypothyroidism; saliva; immunity; antioxidant system; hyaluronic acid